Autocracies and the temptation of sentimentality: repertoires of the past and contemporary meaning-making in the Gulf monarchies - Demmelhuber, Thomas; Thies, Antonia (Third World Quarterly, 2023)
The scholarly debate on the durability of autocracies is vivid. It has explored a broad spectrum of regime types and respective sources and mechanisms of regime survival. A bias towards the strong effect of material means of regime survival, for example repression, cooptation or output-legitimation, is striking. In resource-rich Middle East and North African (MENA) countries, this has been deeply rooted in the logic of rent economies. Only recently have nonmaterial factors of authoritarian power such as emotional engagement or affective behaviour of the populace gained more prominence in the literature, since autocrats are, for example, increasingly trying to strengthen societal bonds by referring to the past. In order to deconstruct this phenomenon in twenty-first-century autocracies, this article introduces sentimentality as a conceptual approach that allows a more fine-grained analysis of contemporary meaning-making attempts on a national level for the sake of regime survival. We assume three dimensions in which forms and functions of sentimentality can be seen–actors, spaces and media–and provide empirical evidence from the Gulf monarchies.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Autocracies; Gulf monarchies; national identity; regime survival; sentimentality

The race for best friendship in Sino-Gulf relations: fractured cooperation and conflict in times of strategic uncertainty - Thies, Antonia; Zumbraegel, Tobias; Demmelhuber, Thomas (International Relations, 2025)
The scholarly debate on a changing Gulf monarchies’ role in international politics has been vividly evolving throughout the last years. It was particularly nurtured by an assumed waning US hegemony in the region and thriving Belt and Road Initiatives of China since 2013. Contributions on the state of Sino-Gulf relations got a massive booster in view of COVID19 since China had presented itself as the most reliable partner with sufficient knowledge and expertise to fight the pandemic. This article is based on the argument that the Gulf monarchies (in our sample: Saudi Arabia, the United Arab Emirates, and Qatar) adjust their foreign policies toward this key player in the Indo-Pacific in order to prepare themselves for strategic uncertainties and security risks on a domestic, regional, and international level. By relying on the expanded IR concept of hedging, we present evidence how this leads to frictions and tensions on the regional level among the Gulf monarchies that have long been described as a like-minded club of authoritarian monarchie